Restoration of the Golden Horn Estuary (Halic) - Coleman, Heather M.; Kanat, Gurdal; Turkdogan, F. Ilter Aydinol (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Restoration of the iconic Golden Horn Estuary in Istanbul, Turkey was a substantial political, logistical, ecological, and social challenge. Forty years of uncontrolled industrial and urban growth resulted in thick layers of anoxic sediment, toxic bacteria, strong hydrogen sulfide odor, and ecologically unlivable conditions. The major components of restoration, spanning two decades, have included (1) demolition and relocation of industries and homes along the shore, (2) creation of wastewater infrastructure, (3) removal of anoxic sludge from the estuary, (4) removal of a floating bridge that impeded circulation, and (5) creation of cultural and social facilities. Although Turkey is not known as an environmental leader in pollution control, the sum of these efforts was largely successful in revitalizing the area through dramatic water quality improvement. Consequently, the estuary is once again inhabitable for aquatic life as well as amenable to local resource users and foreign visitors, and Istanbul has regained a lost sense of cultural identity. This paper focuses on literature review and personal interviews to discuss the causes of degradation, solutions employed to rehabilitate the estuary, and subsequent physicochemical, ecological, and social changes. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Golden Horn Estuary; Istanbul, Turkey; Environmental restoration; Water quality management; Industrial contamination; Sewage pollution; SEDIMENT QUALITY GUIDELINES; WASTE-WATER TREATMENT; ISTANBUL MASTER-PLAN; ENVIRONMENTAL-MODEL; POLLUTED ESTUARY; MANAGEMENT; DISPOSAL; COASTAL; MARINE; REHABILITATION; Engineering; Environmental Sciences & Ecology; Water Resources